Effectiveness of a behavioural intervention to prevent excessive weight gain during infancy (The Baby Milk Trial): study protocol for a randomised controlled trial. Issue 1 (December 2015) - Lakshman, Rajalakshmi; Whittle, Fiona; Hardeman, Wendy; Suhrcke, Marc; Wilson, Ed; Griffin, Simon; Ong, Ken
Abstract Background Infancy is a period of rapid growth and habit formation and hence could be a critical period for obesity prevention. Excess weight gain during infancy is associated with later obesity and formula-fed babies are more likely to gain excess weight compared to breastfed babies. The primary trial outcome is a change in the weight standard deviation score from birth to 1 year. Methods/Design We will recruit 650 to 700 parents who introduce formula-milk feeds within 14 weeks of their baby's birth to a single (assessor) blind, parallel group, individually randomised controlled trial. The focus of the intervention is the caregiver (usually the mother), and the focus of the primary outcome is the infant. The intervention group will receive the behavioural intervention, which aims to reduce formula-milk intake, promote responsive feeding and healthy weaning, and prevent excessive weight gain during infancy. The intervention is based on Social Cognitive Theory and action planning ('implementation intentions'). It consists of three components: (1) a motivational component to strengthen parents' motivation to follow theBaby Milk feeding guidelines, (2) an action planning component to help translate motivation into action, and (3) a coping planning component to help parents deal with difficult situations. It will be delivered by trained facilitators (research nurses) over 6 months through three face-to-face contacts, two telephone contacts and written materials. The control group will have the same number of contacts with facilitators, and general issues about feeding will be discussed. Anthropometric outcomes will be measured by trained research staff, blind to group allocation, at baseline, 6 months and 12 months following standard operating procedures. Validated questionnaires will assess milk intake, temperament, appetite, sleep, maternal quality of life and maternal psychological factors. A 4-day food diary will be completed at 8 months. Discussion The results of the trial will help to inform infant feeding guidelines and to understand the links between infant feeding, behaviour, appetite and growth. Trial registration ISRTCN20814693 . Registration date 13 January 2011.